2017
DOI: 10.1111/den.12918
|View full text |Cite
|
Sign up to set email alerts
|

Peroral endoscopic myotomy as salvation technique post‐Heller: International experience

Abstract: Background Treatment for achalasia has traditionally been Heller myotomy (HM). Despite its excellent efficacy rate, a number of patients remain symptomatic post‐procedure. Limited data exist as to the best management for recurrence of symptoms post‐HM. We present an international, multicenter experience evaluating the efficacy and safety of post‐HM peroral endoscopic myotomy (POEM). Methods Patients who underwent POEM post‐HM from 13 centers from January 2012 to January 2017 were included as part of a prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 12 publications
0
43
0
2
Order By: Relevance
“…Another prospective multicenter study ( n = 51) reported that a clinical response (defined as a decrease in ES ≤3) was achieved in 94% of the cases …”
Section: Clinical Questions and Statementsmentioning
confidence: 98%
“…Another prospective multicenter study ( n = 51) reported that a clinical response (defined as a decrease in ES ≤3) was achieved in 94% of the cases …”
Section: Clinical Questions and Statementsmentioning
confidence: 98%
“…Clinical studies have reported success rates of 92.0-98.0%. [124][125][126] Thus, POEM could be a feasible salvage treatment for patients with persistent symptoms after LHM. However, additional large studies with longer follow-up periods are necessary.…”
Section: Management Of Achalasia Recurrence After Initial Treatmentmentioning
confidence: 99%
“…11,12 A recent randomized trial in treatment naïve patients has shown the efficacy of POEM to be >90% at 2 years when compared with 54% for PD. 13 Moreover, patients with failed LHM and PD and those with end-stage burnt out disease (sigmoid esophagus) also show a good technical and clinical success with POEM [14][15][16] (►Table 1). Taken together, POEM appears to be the panacea for complete spectrum of presentations of achalasia from naïve to treatment failures and also burnt out disease.…”
Section: Per Oral Endoscopic Myotomy (Poem) For Achalasia Cardiamentioning
confidence: 99%